Developing an Instrument to Safeguard Future Generations from Drug Addiction Among Students using Rasch - Nuryono, Wiryo (Fakultas Ilmu Pendidikan Universitas PGRI Kanjuruhan Malang, 2024)
Drug addiction is a chronic disease that attacks the brain and becomes a problem that threatens future generations if it cannot be prevented and overcome. To encourage students to reduce the threat of drugs, an instrument is needed to map students who have high and low resilience. In this case, it is an effort to find out which treatment is appropriate and can prevent the younger generation from being exposed to drugs. So, this research aims to develop a drug addiction instrument and test the validity and reliability of the instrument. This quantitative research uses the RASCH Model to test its validity and reliability. The sample in this study was 2763 junior high school students in Surabaya, East Java, Indonesia. The results of the Rasch model show that in the content validity of the 23 statement items, 11 items were declared valid, 12 items had to be changed, and none of the items were discarded. Meanwhile, the instrument's reliability is 1, which is in the particular category. From the results of the analysis that has been carried out, it can be concluded that the drug addiction instrument can be used to measure adolescents' resistance to the threat of drugs. Keywords: drug addiction; rasch model; assement